An acceptable time - L'ENGLE, MADELEINE; MADELEINE L'ENGLE (New York Bantam Doubleday Dell Books for Young Readers, 1989)
focusing on Polly O'Keefe as she visits her grandparents, Alex and Kate Murry, in Connecticut. She discovers a "time gate" that transports her 3,000 years into the past. There, she is embroiled in a conflict between two prehistoric tribes$1 (Bthe peaceful People of the Wind and the hostile People Across the Lake. s
Keywords: generally defined by consistency, integrity, and proactive, present-focused action; true wisdom involves understanding the deep connection between humanity, nature, and the divine